2015
DOI: 10.4236/as.2015.69088
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Dehydration of Pineapple Stems in Hypertonic Sucrose Solutions

Abstract: The present study provides the evaluation in the influence of the variables: temperature (T), concentration of the osmotic solution (C) and ratio of fruit and osmotic solution (F:OS) during the osmotic dehydration of slices of pineapple stem variety Perola, on the responses: water loss (WL), mass loss (ML), gain of solids (GS) and ratio of gain of solids and water loss (GS/WL). The centesimal composition was determined both in the raw material and in the dehydrated product. To optmize the process, the studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…At high ratio of fruit to solution, viscous nature and dilution effect occur hence the mass transfer coefficient may be lower. dos Santos Filho et al [20] determined that mass transfer coefficient for 3:20 (F:OS) is optimum than 1:20…”
Section: Effect Of Fruit: Solution Ratio and Immersion Time On Normalmentioning
confidence: 99%
See 1 more Smart Citation
“…At high ratio of fruit to solution, viscous nature and dilution effect occur hence the mass transfer coefficient may be lower. dos Santos Filho et al [20] determined that mass transfer coefficient for 3:20 (F:OS) is optimum than 1:20…”
Section: Effect Of Fruit: Solution Ratio and Immersion Time On Normalmentioning
confidence: 99%
“…At high ratio of fruit to solution, viscous nature and dilution effect occur hence the mass transfer coefficient may be lower. dos Santos Falcão [20] determined that mass transfer coefficient for 3:20 (F:OS) is optimum than 1:20 (F:OS) for osmotic dehydration of pineapple stems in hypertonic sucrose solutions. Uddin and Islam [21] reported that 1:5 (F:OS) ratio is optimum for development of shelf stable pineapple product by osmotic dehydration.…”
Section: Influence Of Fruit To Solution Ratio On Nsc For Organic and mentioning
confidence: 99%